Epidemiological changes among patients hospitalized in an internal medicine unit at Hospital Nacional Edgardo Rebagliati Martins in 2008 vs. 2018 - Solari Yokota, Jorge Luis (2024)
Objective: To determine whether epidemiological changes occurred among patients hospitalized in an internal medicine unit at Hospital Nacional Edgardo Rebagliati Martins by comparing data from 2008 and 2018. Materials and methods: An observational, retrospective and cross-sectional study was conducted using an analytical-descriptive approach and a non-experimental design. The study utilized nursing records from 1,640 patients over 18 years of age who were hospitalized in Internal Medicine Unit No. 5 (floor 7C) at Hospital Nacional Edgardo Rebagliati Martins (Jesús María, Lima, Peru) during 2008 and 2018. Sociodemographic variables (sex and age) and clinical variables (unit of origin, type of disease, hospital stay and discharge condition) were analyzed. Data entry and database creation were carried out using Microsoft Excel, while data processing was performed with Microsoft R Open 4.0.2, and Stata 17 was used for data analysis. A descriptive analysis was conducted, presenting the variables as absolute and relative frequencies in tables. The McNemar test was applied to assess the differences in clinical characteristics, and logistic regression models were employed to identify factors associated with mortality. A p value < 0.05 was considered statistically significant. Results: When comparing the two periods, differences were found in the variables sex (OR = 0.60; 95 % CI: 0.50-0.74; p < 0.01), hospital stay (OR = 1.9; 95 % CI: 1.50-2.40; p < 0.01), unit of origin (OR = 0.65; 95 % CI: 0.50-0.85; p < 0.01), mortality (OR = 1.90; 95 % CI: 1.40-2.60; p < 0.01) and type of disease (OR = 0.76; 95 % CI: 0.59-0.97; p = 0.03). No differences were found in the age groups between the two periods. Conclusions: Statistically significant differences suggest an epidemiological transition between the two periods. Therefore, a comprehensive, multidisciplinary and innovative approach is required to improve care for patients with chronic diseases.